Cementless Tritanium Baseplate Total Knee Arthroplasty: Survivorship and Outcomes at 5-Year Minimum Follow-Up - Tarazi, John M.; Salem, Hytham S.; Ehiorobo, Joseph O.; Sodhi, Nipun; Mont, Michael A.; Harwin, Steven F. (The Journal of Knee Surgery, 2020)
Background Newer generation cementless total knee arthroplasty (TKA) designs have provided stronger osteointegration between the implant and bone. Despite excellent survivorship and outcomes with cemented TKAs, areas of concern within the bone–cement interface remain a concern and necessitate studies on alternative constructs. This study assesses: (1) implant survivorship; (2) clinical outcomes; and (3) complications with radiographic outcomes at a 5-year minimum follow-up of cementless highly porous titanium-coated baseplates in TKAs.Methods Part of this study has been reported. We retrospectively reviewed a prospectively collected database at a single high-volume institution between July 1, 2013 and June 30, 2014 for patients who underwent a primary TKA using cementless highly porous titanium-coated baseplate implants. Patients were evaluated clinically at postoperative follow-up visits at a minimum of 5 years. To calculate the survivorship, Kaplan–Meier analysis was performed to determine all-cause, aseptic, and septic implant survivorship at each final follow-up for all patients.Results A total of 228 TKAs were performed and followed for a minimum of 5 years (range, 5–6 years). As of the latest follow-up, one case of septic loosening of the patellar button and one case of patellar dislodgment secondary to physical manipulation were recorded and revised. Overall, the cohort displayed implant survivorship of 99.5% at 5-year minimum follow-up. Improvements were seen in both Knee Society pain and function scores and were 37 points (range, 17–60 points) and 28 points (range, 15–47 points), respectively. The mean improvement in flexion was 17.8 (range, –20 to 40 degrees) and mean improvement in extension was –5.5 (range, –30 to 5 degrees).Discussion Cementless TKAs serve as strong alternative choice to cemented TKAs. Although cemented fixation is commonly known as the gold standard, results of this study confirm the findings of previous investigations on the survivorship of cementless TKA implants. Therefore, patients who undergo primary TKA with a cementless tritanium baseplate can expect excellent clinical outcomes at a 5-year minimum follow-up.
Keywords: TKA; cementless; outcomes